የብራና መጻሕፍት አሠራር እና አዘገጃጀት : ታምራት ሃይሉ (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2023)
Parchment is a writing material which is made of prepared untammed animal skins such as goat, sheep and calf. This practice has been used as a writing medium for over two millennia. The term parchment is often used to refer to any animal skinthat has been scraped or dried under tension. Ethiopian Orthodox Tewahedo Church (EOTC) has giv[1]en rise to rich artistic traditions, including vernacular literature, specifically Ethiopic manuscripts, also known as parchments, after the material on which they are written. Many of the materials needed to create the manuscript, such as parchment, ink, and pen, are fashioned locally, some by the artist himself by transforming goat skin into parchment, a laborious and meticulous process which includes stretching the skin on a wooden frame, removing the hair, washing and drying the skin in the sun or drying room, and repairing any holes. There are different types of manuscripts produced in Ethiopia. Some of them are mätsehaf, ketab or talsam and sənsul. The current study focuses only on the first type. The objective of this paper concentrates on showing and exploring how the birana metsihafoch or books are prepared, processed and worked in Estie wereda, south of Gondar in Amhara regional state. The study follows qualitative research design since it is mainly based on describing, analyzing and interpreting data. That is why; the researcher believs, descriptive method is better suited the study. The main data collection methods are participant observation and semi structural interviews